Assessment of Mangrove Species Composition, Biomass, and Carbon Stock Potential for Climate Change Mitigation in Pekalongan, Indonesia - Ariadi, Heri; Wafi, Abdul; Madusari, Benny Diah; Syakirin, M. Bahrus; Linayati, Linayati; Mardiana, Tri Yusufi (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2026)
Mangrove forests are vital coastal ecosystems that support biodiversity and deliver key ecological services, particularly in tropical regions. In Pekalongan, Central Java, rapid coastal development and land-use change threaten their ecological integrity, particularly their role in carbon sequestration. This study assessed mangrove species richness, biomass, and carbon stock in both conservation and non-conservation areas to evaluate their ecological status and contribution to climate change mitigation. Six sampling sites, comprising protected and unprotected areas, were surveyed using 60 nested square plots to record tree and sapling populations. Biomass estimates, including above and below ground components, were calculated through specific allometric models. Results showed that conservation areas stored higher carbon (248.82 tC ha⁻¹) than non-conservation sites, though Degayu which an unprotected area had the second-highest carbon stock (159.66 tC ha⁻¹). Among species, Sonneratia alba contributed the most carbon, while dense saplings of Rhizophora apiculata and Bruguiera gymnorhiza suggest potential shifts in species dominance. The mean carbon stock (125.02 tC ha⁻¹, equivalent to 495.07 t CO₂e ha⁻¹) indicates substantial emission risks if degradation occurs. These findings underscore the critical role of both conservation and non-conservation mangroves in climate regulation and align with Indonesia’s current policy focus on blue carbon ecosystems, coastal resilience, and community-based conservation.